2020
DOI: 10.1097/icb.0000000000000991
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of Poretti-Boltshauser Syndrome: Findings From Multimodal Imaging and Electrophysiology

Abstract: Background/Purpose: Poretti-Boltshauser syndrome is a rare, nonprogressive neurologic syndrome with characteristic cerebellar cysts on neuroimaging due to mutations in LAMA1. The ophthalmic findings in Poretti-Boltshauser syndrome are not well described. Here, we report the ophthalmic findings from multimodal imaging and electrophysiology of a patient with genetically confirmed Poretti-Boltshauser syndrome.Methods: A 3-year-old boy with confirmed mutations in LAMA1 underwent examination under anesthesia with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Cai et al reported a LAMA1 gene mutation positive case of three years old child having refractive error of 16.50 diopter in both eyes and retinal changes including reduced choroidal thickness .Our index case also had similar refractive error but retinal changes were not appreciated. 5 Alahmadi et al also reported similar case in two-and half-year female child. Important findings were delayed crawling and walking, myopia with cycloplegic refraction of -15 diopter bilaterally and severe retinal thinning.…”
Section: Discussionmentioning
confidence: 71%
“…Cai et al reported a LAMA1 gene mutation positive case of three years old child having refractive error of 16.50 diopter in both eyes and retinal changes including reduced choroidal thickness .Our index case also had similar refractive error but retinal changes were not appreciated. 5 Alahmadi et al also reported similar case in two-and half-year female child. Important findings were delayed crawling and walking, myopia with cycloplegic refraction of -15 diopter bilaterally and severe retinal thinning.…”
Section: Discussionmentioning
confidence: 71%
“…However, the electroretinography findings could be affected because of ischemia and myopic degeneration as well. 10 Cai et al 11 had reported a PBS patient with compound heterozygous mutations in LAMA1 with peripheral nonperfusion areas, corresponding retinal thinning, absence of a distinct foveal avascular zone, and diffuse loss of choriocapillaris architecture with decreased choroidal thickness. However, no such avascular areas were noted in our case clinically.…”
Section: Discussionmentioning
confidence: 99%
“…The LAMA1 protein is, in particular, involved in the cell-cell and cell-extracellular-matrix adhesion, cell motility, and cell migration. A deficient LAMA1 protein typically results in a disruption of the cerebellar folia, especially [31]. Neuroimaging features of PBS resemble findings seen in α-dystroglyconopathies (cerebellar dysplasia with cysts); however, the clinical presentation in PBS is very different (Figure 14).…”
Section: Poretti-boltshauser Syndromementioning
confidence: 97%